Editorial Dossiê Temático - Gislon, Giorgio; Baumgartel, Stephan; Guzzo, Marina; FRaga, Marina; Duenha, Milene; Pires, Rafaela Blanch (Urdimento - Revista de Estudos em Artes Cênicas, 2026)
Informações sobre o conteúdo do Dossiê Temático: Dossiê Artes vivas e o Antropoceno/Capitaloceno II